2014
DOI: 10.1021/ma500506r
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Irreversible Chain Adsorption

Abstract: Recent experimental evidence showed a strong correlation between the behavior of polymers under confinement and the presence of a layer irreversibly adsorbed onto the supporting substrate, hinting at the possibility to tailor the properties of ultrathin films by controlling the adsorption kinetics. At the state of the art, however, the study of physisorption of polymer melts is mainly limited to theory and simulations. To overcome this gap, we present the results of an extensive investigation of the kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
180
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(212 citation statements)
references
References 25 publications
29
180
3
Order By: Relevance
“…The number of available monomers is established by the monomer density and the number of chains making a contact with a flat wall per unit surface ( N −1/2 ) . The number of monomers adsorbed per units of surface at any given time is thus proportional to N 1/2 , while the chain adsorption rate is molecular weight independent …”
Section: Kinetics Of Irreversible Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of available monomers is established by the monomer density and the number of chains making a contact with a flat wall per unit surface ( N −1/2 ) . The number of monomers adsorbed per units of surface at any given time is thus proportional to N 1/2 , while the chain adsorption rate is molecular weight independent …”
Section: Kinetics Of Irreversible Adsorptionmentioning
confidence: 99%
“…After drying, the residual adsorbed layer is finally ready for investigation. Nowadays a large number of different experimental techniques, ranging from ellipsometry to atomic force microscopy, X‐rays scattering, fluorescence and dielectric spectroscopy, have been employed to analyze the intriguing properties of these extremely thin films.…”
Section: Introductionmentioning
confidence: 99%
“…This annealing corresponds to 4 × 10 14 τ α , which by far exceeds the longest equilibration time for polystyrene thin films of a similar MW [44]. However, such strong annealing did not produce any detectable changes in the dielectric spectra or their temperature dependence (Fig.S4).…”
mentioning
confidence: 92%
“…We see two possible reasons for this unexpected behavior: (1) PNCs require long annealing time to reach equilibrium [43,44]; or (2) the polymer chains experience a strong frustration in chain packing in the interfacial region due to the formation of large loops at higher MW. Recent studies of supported thin polymer films revealed a strong MW dependence of the equilibrium desorption times.…”
mentioning
confidence: 96%
See 1 more Smart Citation